Penerapan Strategi Pembelajaran Aktif Question Student Have Untuk Meningkatkan Kemampuan Berpikir Kritis Matematik Siswa SMK - Windi Wiliawanto; Martin Bernard; Padillah Akbar; Asep Ikin Sugandi (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2019)
This study aims to understand and improve the thinking ability of vocational mathematics students with active Question Student Have. This research is an experimental study. To see the suitability of the implementation of learning with this strategy, validation was carried out on the observation sheet and the implementation plan of learning. The subjects of this study were class XI TKJ 2 Penida Vocational School 2 Katapang 2016/2017 academic year (35 students). This strategy is used to get hopes and problems in mathematics learning written on the question card. The instrument used is a matter of description. . Data in the implementation of the application through a sheet of activities and learning outcomes compiled at the end of learning, a tool used to process pretest and posttest data from the results of using a computer with Minitab 16 software. Using the application of mathematics Question Student Have Strategies Owned by Students. The results of the research conducted on the Application of Active Question Student Have to Vocational Critical Mathematical Thinking Ability of students concluded that "the mathematical thinking ability of Vocational students through active learning strategies type of Student Questions Ask better about what is considered for mathematics students who learn to use learning models conventional.